Validated stability-indicating methods for the determination of zafirlukast in the presence of its alkaline hydrolysis degradation product - Amal M. Abou Al Alamein (Faculty of Pharmacy, Cairo University, 2012)
Three simple stability-indicating methods for the analysis of Zafirlukast (ZAF) in the presence of its alkaline degradation products were developed and validated as per the International Conference on Harmonization (ICH) guidelines to evaluate the stability-indicating power of the proposed methods. The developed high-performance liquid chromatographic technique was achieved on ZORBAX-ODS (5 μm, 150 × 4.6 mm, i.d.) by isocratic elution with a mixture of acetonitrile/0.05 M phosphate buffer, pH 5.0, (50:50; v/v) as a mobile phase at flow rate of 1.0 mL min−1, followed by UV detection at 240 nm. The method could determine ZAF in the range of 2-40 μg mL−1 with a mean percentage recovery of 99.73 ± 0.903. The proposed HPLC method was utilized to investigate the kinetics of alkaline degradation of ZAF. First derivative of the ratio spectra (1DD) method was applied to analyze the drug under investigation without any interference from its degradation product with a linearity range of 4-32 μg mL−1 and with a mean percentage recovery of 99.85 ± 0.608. A chemometric method was also developed using the partial least squares (PLS) model for selective determination of ZAF in the range of 4-40 μg mL−1, the mean percentage recovery was found to be 100.00 ± 0.336.